Determinants of Job Satisfaction and it’s Implication on Employee Performance of Port Enterprises in DKI Jakarta - Barasa, Larsen; Gunawan, April; Sumali, Bambang (International Review of Management and Marketing, 2018)
This study aims to examine the determinants of employee job satisfaction and its implications on employee performance at Port Enterprises in DKI Jakarta. Population in this research is employees at Port Enterprises. Samples of data amounted to 264 employees and retrieval for instrument test 90 people so that the study population is 421 people. To prove the hypothesis of this study using data collected by statistics, both descriptive and inferential, namely Structural Equation Modeling (SEM), consists of sub - structure: work competence, work motivation and organizational culture as exogenous variables and job satisfaction and performance as endogenous variables. The main structure consists of work competence, work motivation and organizational culture as exogenous variable and job satisfaction as intervening variable and performance as endogen variable. The results showed: (1) There is positive influence and significant work competence to job satisfaction of employees in Port Enterprises DKI Jakarta. (2) There is positive and significant influence of work motivation on job satisfaction of employees. (3) There is a positive and significant influence of organizational culture on employee job satisfaction, where more dominant variable affecting job satisfaction is a variable Competence. (4) There are positive and significant influence of work competence, work motivation and organizational culture together to job satisfaction of employees. (5) There is a positive and significant influence of work competence on employee performance. (6) There is a positive and significant influence of work motivation on employee performance. (7) There is a positive and significant influence of organizational culture on the performance of employees. (8) There is a positive influence and significant job satisfaction on the performance of employees. (9) There are positive and significant influence of work competence, work motivation, organizational culture and job satisfaction together to employee performance, where more dominant variable affecting employee performance is a variable Job satisfaction. From equation structure obtained, it can be concluded by the Square Multiple Correlation (R2) employee performance of 85% is affected by the variable work competence, work motivation, organizational culture and job satisfaction. Job Satisfaction is as full mediating. Employee performance Port Enterprises DKI Jakarta can be improved by improving the work competence, work motivation, organizational culture and job satisfaction. Keywords: Work Competence, Work Motivation, Organizational Culture, Job Satisfaction, Employee Performance JEL Classifications: M12, N30, Q15 https://doi.org/10.32479/irmm.6993